Intergenerational Subalternity and the Resistance of Balinese Women in the Novel Racun Puan - Devy Selpia (Universitas Negeri Surabaya, 2026)
The novel Racun Puan by Ni Nyoman Ayu Suciartini presents the stories of three Balinese women across generations: Ibu Aruna, Aruna, and Samudra. Each of them is subjected to a distinct yet interconnected form of silencing, forming a chain of intergenerational subalternity. This study applies Gayatri Spivak's postcolonial theory to examine two aspects: the identification of Balinese women as subaltern figures in the novel Racun Puan, and the forms of resistance enacted by those subaltern characters. A qualitative descriptive-analytical method was employed, with data gathered from the novel through reading, observation, and documentation techniques. Analysis was conducted through Spivak's key concepts of political and cultural representation, epistemic violence, and resistance. The findings demonstrate that subalternity operates across generations through the internalization of patriarchal values, a process this study terms